Nutritional status of Under Five Years children of Falluga refugees - Mahdi, K.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In 2005 Falluga city had an humanitarian crisis situation, characterized by armed conflict. Larg population displaced. To assess the nutritional status of under five children, a check of 678 child in five places of Internal Displaced Peoples . was achieved The results indicated that 19.6%, 48.5% of the children had diarrhea and acute respiratory infection. Twenty percent of the children had achronic malnutrition while 4.1% & 0.5% had a general and acute malnutrition.